Iron and sulfur isotope constraints on redox conditions associated with the 3.2 Ga barite deposits of the Mapepe Formation (Barberton Greenstone Belt, South Africa). (1st August 2017) - Busigny, Vincent; Marin-Carbonne, Johanna; Muller, Elodie; Cartigny, Pierre; Rollion-Bard, Claire; Assayag, Nelly; Philippot, Pascal
Abstract: The occurrence of Early Archean barite deposits is intriguing since this type of sediment requires high availability of dissolved sulfate (SO4 2− ), the oxidized form of sulfur, although most authors argued that the Archean eon was dominated by reducing conditions, with low oceanic sulfate concentration (<10 μM) relative to present day levels of 28, 000 μM. In order to better assess the redox state of the paleo-atmosphere and -oceans, we examined Fe and S isotope compositions in a sedimentary sequence from the 3.2 Ga-old Mendon and Mapepe formations (Kaapvaal craton, South Africa), recovered from the drill-core BBDP2 of the Barberton Barite Drilling Project. Major elements were also analyzed to constrain the respective imprints of detrital vs metasomatic processes, in particular using Al, Ti and K interrelations. Bulk rock Fe isotope compositions are linked to mineralogy, with δ 56 Fe values varying between −2.04‰ in Fe sulfide-dominated barite beds, to +2.14‰ in Fe oxide-bearing cherts. δ 34 S values of sulfides vary between −10.84 and +3.56‰, with Δ 33 S in a range comprised between −0.35 and +2.55‰, thus supporting an O2 -depleted atmosphere (<10 −5 PAL). Iron isotope variations together with major element correlations show that, although the sediments experienced a pervasive stage of hydrothermal alteration, the rocks preserved a primary/authigenic signature predating subsequent hydrothermal stage. Highly positive δ 56 Fe values recorded in primary Fe-oxides from ferruginous cherts support partial Fe oxidation in a reducing oceanic environment (O2 < 10 −4 μM), but are incompatible with a model of complete oxidation at the redox boundary of a stratified water column. Iron oxide precipitation under low O2 levels was likely mediated by anoxygenic photosynthesis, and/or abiotic photo-oxidation processes. Our results are consistent with global anoxic conditions in the 3.2 Ga-old sediments, implying that the barite deposits were most likely sourced by atmospheric photolysis of S gases produced by large subaerial volcanic events, and possibly SO4 2− produced by magmatic SO2 disproportionation in hydrothermal systems.